Dasatinib as a Potential Targeted Therapy for Chronic Pancreatitis: A Narrative Review of Macrophage-PSC Interactions - Purnomo, Anton; Suyata (Biomedical Journal of Indonesia, 2025)
Chronic pancreatitis is a long-term inflammatory condition affecting the pancreas, with progression worsening over time. One of the effects of this disease is the formation of scar tissue, which can permanently damage the pancreas and disrupt its functions, both exocrine and endocrine. Chronic pancreatitis can result in various serious complications and even be fatal. In the effort to treat chronic pancreatitis, therapies targeting macrophages have begun to attract attention as an innovative approach. One of the drugs in the spotlight is dasatinib, a tyrosine kinase inhibitor, which has shown the ability to alter the inflammatory response by affecting the macrophage population in the pancreatic microenvironment. This literature review aims to dig deeper into the role of dasatinib in the treatment of chronic pancreatitis and explain the pathophysiology of this disease, especially how macrophage activation contributes to the inflammatory process, as well as the therapeutic effects of dasatinib, we can find new insights to develop more effective treatment strategies.